ANALISIS POLA DAN RESIKO USAHA GULA AREN DI KABUPATEN REJANG LEBONG - Kencana, Felycia Tiera; Sukiyono, Ketut; Sumantri, Bambang (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2012)
This study is aimed at examining enterprises model and analysing risk level of Palm Sugar in Rejang Lebong Regency. Risk Analysis involve nira harvested, nira processed, palm sugar production, and palm sugar prices received by producers. Twostages cluster sampling method is used to determine research areas, i.e, subdistrict of Sindang Kelingi and Selupu Rejang based on the numbers of firms. Using similar critirea, two villages are selected, i.e, Air Meles Atas and Sindang Jati. From those villages, then, 86 palm sugar producers are selected using Simple Random Sampling. Descriptive analysis is applied to describe entreprises model of palm sugar industries while risks is analysed using its varians, standard deviation, and minimum level of production as proposed by Maryam and Suprapti (2008). The research shows that all palm sugar industries in this regency can be categories as home industries with average production scale of 11.58 kg per process in rainy season and 11. 54 kg in dry season. Palm sugar producers use their own capital to produce palm sugar and borrowed to palm sugar village merchants when they need. From risk analysis, the study finds that palm sugar producers will face higher risk in term of nira harvested and processed, and production in dry season, except in term of price received which is higher in rainy season. Over all, palm sugar producers will not face risk significantly both in dry and rainy season.